Effect of Microsprinkler Fertigation on Growth and Yield of Rabi Onion - M Prabhakar (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2011)
A field experiment was conducted during rabi 2005-2006 at Indian Institute of Horticultural Research, Bangalore, to study the performance of onion cv. Arka Niketan as influenced by microsprinkler fertigation using different sources and levels of fertilizers. Results indicated that crop growth in terms of leaf production, plant height, radial and equatorial diameter was not significantly influenced by the treatments. Fertigation treatments were superior for marketable bulb yield as compared to soil application of fertilizer. Also bulb yield through soil application of fertilizer increased by changing over from surface-irrigation to microsprinkler irrigation. However, bulb yield did not significantly decrease by applying just 75% of the recommended NPK fertilizers, using common or water soluble fertilizers supplied through fertigation. For achieving maximum yield, however, it is recommended to apply 100% recommended dose of fertilizers through sprinkler fertigation using water soluble fertilizers.